2011
DOI: 10.1007/s10531-011-0083-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of arthropods in subtropical rice growing areas in the Brazilian south

Abstract: This paper describes a survey of arthropods in rice-growing areas of Rio Grande do Sul, Brazil, undertaken to identify the main groups of insect pests and their natural enemies present in three producing regions during the stages of crop development. The study was conducted during the crop years 2007/2008 and 2008/2009 in the municipalities of Cachoeira do Sul, Eldorado do Sul and Capivari do Sul. A total of 44,231 arthropods were collected: 26,821 in 2007/2008 and 17,410 in 2008/2009. Spatial and temporal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Other authors have also reported individuals of Eulophidae in rice crops (Nacro et al, 1997;Williams et al, 1999;Bayegan et al, 2015), and Gumovsky et al (2006) described a new species of Eulophidae, genus Closterocerus, parasitoid of Dicladispa armigera (Olivier, 1808) (Coleoptera: Chrysomelidae), a major rice pest in Southeast Asia and Australasia. In rice cultivation in Rio Grande do Sul, Eulophidae also was the most abundant parasitoid family and the phytophagous registered were Curculionidae, Pentatomidae, Delphacidae and Cicadellidae (Fritz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also reported individuals of Eulophidae in rice crops (Nacro et al, 1997;Williams et al, 1999;Bayegan et al, 2015), and Gumovsky et al (2006) described a new species of Eulophidae, genus Closterocerus, parasitoid of Dicladispa armigera (Olivier, 1808) (Coleoptera: Chrysomelidae), a major rice pest in Southeast Asia and Australasia. In rice cultivation in Rio Grande do Sul, Eulophidae also was the most abundant parasitoid family and the phytophagous registered were Curculionidae, Pentatomidae, Delphacidae and Cicadellidae (Fritz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rice fields harbour a rich and varied fauna than any other agricultural crop (Heckman, 1979;Fritz et al, 2011). The fauna is dominated by micro, meso and macro arthropods inhabiting the soil, water and vegetation sub-habitats of the rice fields.…”
Section: Introductionmentioning
confidence: 99%
“…In these ecosystems, arthropods are found in an intermediate position in the food chain and include herbivores, saprophytes, parasites and predators of other animals (Fritz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%